(untitled) (Sociologisk Forskning, 2007)
The controversy of growth: a debate between economists and sociologists about the Swedish public sector Has the ‘Swedish model’ forced Sweden into stagnating economic growth? And has this caused Sweden to lag behind other comparable OECD-countries from the 1970s and onwards, i.e. since Sweden chose a welfare path different from many other countries? This has been the subject of a more than twenty year long controversy between Walter Korpi, professor of sociology and social policy, and leading Swedish mainstream economists. In a series of articles, especially during the years of economic crisis in the 1990s, Walter Korpi claimed that other reasons than the Swedish model has to be taken into account when comparing welfare states and their impact on economic growth, while the economists have persistently maintained the opposite view. These disputes over statistics and methodology have developed into what is here referred to as a science based controversy. This article analyzes the controversy between sociology and economy in accordance with controversy theory. In this way we can consider both the underlying social as well as political aspects of the debate, which leads to the conclusion that not every aspect of a science-based controversy is a byproduct of science itself.